Enveromental problems of Vestern Caspean agricural landskape. Ways of their decision - A. A. Ajtemirov; G. N. Gasanov; M. R. Muaev; S. M. Gasanova (Юг России: экология, развитие)
Struggle against desertification of Northwest Caspian territories, ajonsidewith prevention of natural fodder lands degradation, should from agricultural system of pure streams and ground machining. Land improvement with use of Sorghum vulgare P., Medicago sateva L., Elytrigia elongata, Agrohyrum Pestiniforme R. is perspective for desrease of aoils salinity.